Análise da ressuscitação cardiopulmonar intra-hospitalar em adultos utilizando o Estilo Utstein - Bruna Adriene Gomes de Lima e Silva (2013)
The protocol In-hospital Utstein Style (US) was published in 1997 in order to standardize relevant information on cardiopulmonary resuscitation (CPR) and make it possible to compare results between different hospitals. In Brazil, the literature is scarce on studies with data obtained through the US. Objective: To analyze the clinical profile of patients with in-hospital cardiopulmonary arrest (CPA), their care and evolution based on data recorded according to US. Method: observational and longitudinal study carried out in intensive care setting of two hospitals with patients who presented CRP in 12 months, using data recorded according to US. Results: We studied 89 patients with a mean age of 59 ± 17.6 years, 46 (51.6%) males who had 96 CPA and were submitted to CPR maneuvers. The most common comorbidities were hypertension and diabetes mellitus, 45 (50.5%) were diagnosed with heart disease and the most frequent diagnosis at admission was acute myocardial infarction (AMI) (22 patients, 24.7%). It was found that 64.6% of episodes of CPA occurred during the daytime, asystole was the most frequent initial rhythm (41 patients, 42,7%) with ventricular fibrillation or tachycardia detecte in 14 patients (14.6%). The main causes of CRP were hypotension (30.2%), respiratory depression (14.6%) and myocardial ischemia (12.5%). Most of the patients who presented return of spontaneous circulation (ROSC) evolved with relapsing CPA that occurred mainly in the first 24 hours after initial CPA (35 of the 63 episodes of recurrence, 61.4%). Mean time interval between admission and the occurrence of CPA was 10.3 days, median of 5 days. Time interval between CPA and CPR was 0.68 min, the mean duration of CPR was 16.3, median 11 min and defibrillation was performed in 7.1 min (median = 7.0 min.) after beginning of CPR. The average interval between CPA and drug administration was 2.5 min (90% adrenaline, atropine in 38.5% of CPR). Immediate survival of patients after CPA was 71% and survival to hospital discharge and at six months after discharge was only 9 and 6%, respectively. There were associations (Mann-Whitney and chi-square) between sex and duration of CPR (19.2 min in women versus 13.5min for men, p = 0.02) and duration of CPR and ROSC (10.8 min versus 30.7 min, p = 0.00). There was also an association between heart disease and age (p = 0.00, 60.6 versus 53.6 years for those with and without heart disease, respectively) as well as between heart disease and dobutamine administration during CPR (29.1% versus 12.5%, p = 0.03), diagnosis of AMI at admission and frequency of intubation (45.8% versus 15.2%, p = 0.00) and the score on the Glasgow coma scale (13.1 versus 9.0 for other diagnoses at admission, p = 0.00). Conclusions: Prognosis of CPA in our series composed of patients who had this complication during intensive care unit stay was poor, since only eight (9%) patients were discharged from the hospital and only five (6%) suvived until the sixth month after hospital discharge.